WELL COMPLETION PROCESSES THROUGH ADVANCED SUBSEA EQUIPMENT INTEGRATION: A COMPREHENSIVE ANALYSIS OF EFFICIENCY AND RELIABILITY - Elvin Hajiyev (Galaxy International Interdisciplinary Research Journal, 2023)
In order to facilitate the production and transfer of hydrocarbons from offshore reservoirs, installing and connecting a variety of equipment and systems on the seafloor is known as subsea well completion. This is a difficult and complicated process. Subsea well completion process design and optimization need taking into account a number of variables, including environmental effect, dependability, and efficiency. The state-of-the-art methods and technologies for subsea well completion are reviewed in this article, along with the ways that advanced subsea equipment like compression, boosting, and subsea processing can improve the sustainability and performance of subsea production systems. We furthermore pinpoint the primary obstacles and prospects for the assimilation and execution of these technologies within the oil and gas sector.